2021
DOI: 10.3390/cells10092287
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids DHA and EPA Reduce Bortezomib Resistance in Multiple Myeloma Cells by Promoting Glutathione Degradation

Abstract: Multiple myeloma (MM) is a hematological malignancy that exhibits aberrantly high levels of proteasome activity. While treatment with the proteasome inhibitor bortezomib substantially increases overall survival of MM patients, acquired drug resistance remains the main challenge for MM treatment. Using a combination treatment of docosahexaenoic acid (DHA) or eicosapentaenoic acid (EPA) and bortezomib, it was demonstrated previously that pretreatment with DHA/EPA significantly increased bortezomib chemosensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 63 publications
(93 reference statements)
0
22
0
Order By: Relevance
“…Besides the MAPK signaling, our results highlighted the involvement of ERK signaling in ferroptosis targeted by GSH. ERK signaling is associated with ferroptosis in many cancers, including multiple myeloma ( Chen J. et al, 2021 ), endometrial carcinoma ( Qin et al, 2021 ), hepatocellular carcinoma ( Fei et al, 2021 ), and pancreatic cancer ( Ye et al, 2020 ). Specifically, the ERK signaling pathway has been linked with ferroptosis and associated with the prognosis of OC ( Chen R. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the MAPK signaling, our results highlighted the involvement of ERK signaling in ferroptosis targeted by GSH. ERK signaling is associated with ferroptosis in many cancers, including multiple myeloma ( Chen J. et al, 2021 ), endometrial carcinoma ( Qin et al, 2021 ), hepatocellular carcinoma ( Fei et al, 2021 ), and pancreatic cancer ( Ye et al, 2020 ). Specifically, the ERK signaling pathway has been linked with ferroptosis and associated with the prognosis of OC ( Chen R. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) supplementation of MM cells, prior the treatment with BTZ, potently decreased cellular GSH levels and altered the expression of related metabolites and key enzymes involved in GSH metabolism, suggesting a critical role of GSH degradation in overcoming BTZ resistance in MM. In addition, the NRF2–ATF3/AFT4–ChaC glutathione specific gamma-glutamylcyclotransferase 1 (CHAC1) signaling pathway was shown to be potentially implicated in DHA/EPA pretreatment-mediated GSH degradation ( 282 ).…”
Section: Metabolic Factors Promoting Resistance To Pi In MMmentioning
confidence: 99%
“…Studies have shown that iron exposure can reduce the activity of the proteasome, hence increasing the efficacy of Bortezomib and Carfilzomib (the second generation of proteasome inhibitors used for MM therapy) in MM cells and leading to severe MM cell death by promoting ferroptosis ( 113 ). In order to overcome the drug resistance of Bortezomib, docosahexaenoic acid or eicosapentaenoic acid in combination with Bortezomib were used to enhance the sensitivity of MM cells to Bortezomib ( Table 1 ) ( 114 ). Specifically, docosahexaenoic acid and eicosapentaenoic acid can modulate the redox balance in MM cells by reducing the content of GSH in MM cells, thus improving the therapeutic effect of Bortezomib.…”
Section: Role Of Ferroptosis In Hematologic Malignancies Treatmentmentioning
confidence: 99%